Effectiveness of Transition Theory-Based Interventions on Outcomes of Nursing Care: A Scoping Review - Roya Khorrami Estakhri; Zahra Taheri Ezbarami; Hamid Peyrovi; Ehsan Kazemnezhad Leyli; Adele Isanazar; Seyed Aboozar Fakhrmousavi; Fateme Jafaraghaee (Iranian Journal of Nursing and Midwifery Research)
Background: Transition theory addresses the experiences of coping with changes in stages, roles, identities, situations, or positions. It emphasizes understanding the nature of these changes, facilitating and supporting the experience and response at various stages, and maintaining health before, during, or after the transition process. This study examined the effects of “transition theory-based interventions” on nursing care outcomes. Materials and Methods: This scoping review followed the methodology proposed by Arksey and O’Malley. A comprehensive search was conducted across ProQuest, Scopus, PubMed, ScienceDirect, ResearchGate, and Google Scholar to identify studies where transition theory-based interventions were utilized as an independent variable in interventional designs. Identified studies underwent a four-stage screening process, and the final selection was made based on predefined inclusion and exclusion criteria. The screening process is detailed in the PRISMA diagram. Results: Of the 476 articles initially identified, 24 were shortlisted for further review. After applying the inclusion criteria, 11 studies focusing on care interventions grounded in transition theory were included. These comprised five randomized clinical trials and six quasi-experimental studies. A synthesis of the findings revealed that transition theory-based interventions significantly improved various outcomes, including quality of life, hope, self-efficacy, readmission rates, caregiver burden, and role mastery. Conclusions: Implementing nursing care interventions grounded in nursing theories, such as transition theory, is critical to bridging the gap between theory and practice. Transition theory-based care tailored to individuals undergoing diverse transitional experiences can enhance positive outcomes in nursing care.